Characteristics and Determinants of Partial Remission in Children with Type 1 Diabetes Using the Insulin-Dose-Adjusted A1C Definition - Aurore Pecheur; Thierry Barrea; Valérie Vandooren; Véronique Beauloye; Annie Robert; Philippe A. Lysy (Journal of Diabetes Research)
To evaluate the characteristics and determinants of partial remission (PR) in Belgian children with type 1 diabetes (T1D), we analyzed records of 242 children from our center. Clinical and biological features were collected at diagnosis and during follow-up. PR was defined using the insulin-dose-adjusted A1C definition. PR occurred in 56.2% of patients and lasted 9.2 months (0.5 to 56.6). 25.6% of patients entered T1D with DKA, which correlated with lower PR incidence (17.6% versus 82.3% when no DKA). In our population, lower A1C levels at diagnosis were associated with higher PR incidence and in young children (0–4 years) initial A1C levels negatively correlated with longer PR. Early A1C levels were predictive of PR duration since 34% of patients had long PRs (>1 year) when A1C levels were ≤6% after 3 months whereas incidence of long PR decreased with higher A1Cs. C-peptide levels were higher in patients entering PR and remained higher until 3 years after diagnosis. Initial antibody titers did not influence PR except for anti-IA2 titers that correlated with A1C levels after 2 years. Presence of 2 versus 1 anti-islet antibodies correlated with shorter PR. PR duration did not influence occurrence of severe hypoglycemia or diabetes-related complications but was associated with lower A1C levels after 18 months. We show that, at diagnosis of T1D, parameters associated with β-cell mass reserve (A1C, C-peptide, and DKA) correlate with the occurrence of PR, which affects post-PR A1C levels. Further research is needed to determine the long-term significance of PR.